Rossi, Maria Alessia and Alice Isabella Sullivan, eds. Eclecticism in Late Medieval Visual Culture at the Crossroads of the Latin, Greek, and Slavic Traditions (Sense, Matter, and Medium 6). Berlin, Boston: De Gruyter, 2022 [ISBN: 9783110693164] - Mickūnaitė, Giedrė (Eikón / Imago, 2024)
Book review of Rossi, Maria Alessia and Alice Isabella Sullivan, eds. Eclecticism in Late Medieval Visual Culture at the Crossroads of the Latin, Greek, and Slavic Traditions (Sense, Matter, and Medium 6). Berlin, Boston: De Gruyter, 2022 [ISBN: 9783110693164]